Lesbian gay bisexual transgender and intersex (LGBTI) students are scrambling for access to healthcare services in the campus healthcare system: Perceptions of key informants - Kleinhans, A.V. (South African Journal of Higher Education, 2019)
This article explores the experiences of lesbian, gay, bisexual, transgender and intersex (LGBTI) students and focuses specifically on how they access healthcare in the campus health system at a university in South Africa. Semi-structured, in-depth key informant interviews were conducted with selected representatives from all service providers in the campus healthcare system including a gender expert and a student leader. The findings of this study show that LGBTI students are underserved in the campus healthcare system and this is the result of a heteronormative campus environment. The implications of this study suggest the critical need for support from university management, student mobilisation, and sensitisation training for healthcare providers.